Histidine-dependent protein methylation is required for compartmentalization of CTP synthase - Lin, W; Chakraborty, A; Huang, S; Wang, P; Hsieh, Y; Chien, K; Lee, Y; Chang, C; Tang, H; Lin, Y; Tung, C; Luo, J; et al. (Elsevier, 2018)
CTP synthase (CTPS) forms compartmentalized filaments in response to substrate availability and environmental nutrient status. However, the physiological role of filaments and mechanisms for filament assembly are not well understood. Here, we provide evidence that CTPS forms filaments in response to histidine influx during glutamine starvation. Tetramer conformation-based filament formation restricts CTPS enzymatic activity during nutrient deprivation. CTPS protein levels remain stable in the presence of histidine during nutrient deprivation, followed by rapid cell growth after stress relief. We demonstrate that filament formation is controlled by methylation and that histidine promotes re-methylation of homocysteine by donating one-carbon intermediates to the cytosolic folate cycle. Furthermore, we find that starvation stress and glutamine deficiency activate the GCN2/ATF4/MTHFD2 axis, which coordinates CTPS filament formation. CTPS filament formation induced by histidine-mediated methylation may be a strategy used by cancer cells to maintain homeostasis and ensure a growth advantage in adverse environments.